ANALISIS KEPUASAN PASIEN DITINJAU DARI KINERJA KARYAWAN PADA RUMAH SAKIT UMUM DAERAH (RSUD) SARAS HUSADA PURWOREJO - Ariya Fitriastuti; Agus Fitri Yanto (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2018)
Hospital as a entity sought to develop good corporate governance with services variety, including the indicators of a comprehensive performance development. Patients as health services consumers certainly expect optimum service from the hospital, be it from a doctor, nurse or from other employees. If the services provided by the hospital as expected, then the patient is likely to feel satisfied. That patients have the satisfaction of the hospital can emphasize a quality service form. This study aimed to determine patient satisfaction in terms of the employees performance at the Saras Husada Regional General Hospital Purworejo. The population in this study were inpatients and outpatients in the Saras Husada hospital with an unknown number while the sample in this study is part of inpatients and outpatients as many as 110 people. The instrument used in this study is Patient Satisfaction Questionnaire and Performance Employees have previously been tested and qualified for the validity and reliability while data analysis using multiple regression analysis. Results of t-test analysis note that the significance values greater reliability and responsiveness of the condition of the test criteria of 0.05 (5%). This means that reliability and responsiveness did not significantly influence patient satisfaction in Saras Husada hospital. Meanwhile, the significant value assurance, empathy and tangible terms is smaller than the test criteria of 0.05 (5%). This means assurance, empathy and tangible significantly influence patient satisfaction in hospitals Saras Husada Purworejo. F-test analysis results known that test-f value of 64.608 with a significance value of 0.000 is less than 0.05 means that the independent variable is the employees performance consisting of reliability, responsiveness, assurance, empathy and tangibles simultaneously significant effect on patient satisfaction in Saras Husada Hospital Purworejo.